Frontiers of seismology. Issue 4 (1st August 2020) - Ziolkowski, Anton; Bell, Andrew; Browitt, Christopher; Curtis, Andrew; Macdonald, Calum; Main, Ian; Peacock, Sheila; Rawlinson, Nicholas; Storchak, Dmitry; Walker, Alice
Abstract : Anton Ziolkowski and co-organizers look back at the British Seismology Meeting 2019, which discussed events of all scales as well as new hardware and software techniques Abstract: Anton Ziolkowski and fellow organizers look back at the British Seismology Meeting 2019, which discussed events of all scales as well as new hardware and software techniques.